The Effect of Exchange Rate on Sino-EU and Sino-US Trade - Zhang, Hailun (Asian Journal of Economic Modelling, 2017)
The EU and the United States are China’s first and second largest trade partners respectively. This paper selects monthly data between January 2002 and December 2016 including real exchange rate and import & export volume. Cointegration equations and vector error correction models are built for capturing long-term relationships among variables. Besides, impulse response function and variance decomposition are applied to analyze short-run dynamic characteristics of impacts of exchange rate on trade. Results show there are long-term steady relationships between imports & exports and real exchange rate. It is also found that the RMB devaluation can harm to Sino-EU import but benefit for Sino-EU export and Sino-US trades, while Marshall-Lerner condition only establishes in Sino-EU trade. However, the strength China needs to improve trade with the Euro Zone is not as much as with the US. In a short run, the shock from exchange rate has more durable impact on Sino-EU import, but exchange rate is a most important factor only for Sino-EU export. Therefore, current depreciation of RMB have little impact on Sino-EU and Sino-US trades.